140k views
2 votes
Please help me!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!ASAP!!!!!!!!!!!!!!!!!!!!!!!!!!!

Please help me!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!ASAP!!!!!!!!!!!!!!!!!!!!!!!!!!!-example-1
User Bendlas
by
5.2k points

1 Answer

7 votes

Using the formulas :

A=2AB+(a+b+c)h

AB=√(s(s﹣a)(s﹣b)(s﹣c) )

s = (a+b+c) / 2

Solving for A:

A=ah+bh+ch+1 /2 √(﹣a∧4+2(ab)∧2+2(ac)∧2﹣b∧4+2(bc)∧2﹣c∧4)

=2·1.7+3·1.7+2·1.7+1 /2· √(﹣2∧4+2·(2·3)∧2+2·(2·2)∧2﹣3∧4+2·(3·2)∧2﹣24)

≈15.86863

User Saikou
by
6.3k points